Biological Roles of Cyanobacterial Topoisomerase I - Shilpa Dhaka; Anamica; Everest Shiwach; Sandeep Kumar; Suman Verma (International Journal of Engineering and Management Research, 2021)
A double helical macromolecule DNA, that carries all the genetic instruction found inside the nucleus, consists of two strands that wind around each other, to form a structure called double helix. This double helix undergoes various important processes such as replication, recombination, transcription and repair to derive information and exchange them to next generation. So, during these processes relaxation of DNA is require then there comes a roles of DNA topoisomerases that works on ATP independent manner, cut at one strand of DNA and ligate them itself. This review shows the roles and mechanism action of bacterial topoisomerases.